2008
DOI: 10.1007/s10620-008-0207-0
|View full text |Cite
|
Sign up to set email alerts
|

Antral Inflammatory Cells, Gastric Emptying, and Electrogastrography in Pediatric Functional Dyspepsia

Abstract: The aims of the current study were to determine the activation states of antral eosinophils and mast cells and to evaluate the interactions of antral inflammatory cells with gastric emptying and electrogastrography (EGG) in 30 pediatric patients with functional dyspepsia. Eosinophil degranulation was moderate in 42% and extensive in 54% of patients. Mast cell degranulation was > 50% in 81% of patients. Elevated mast cell density was associated with slower one hour gastric emptying and increased preprandial dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 35 publications
0
42
1
Order By: Relevance
“…Histopathological findings of the present study, confirming that antral eosinophils were significantly activated in children with FD, are consistent with the results of a previous study. 37 The results of this present study is different with that of previous studies except for Friesen et al's study, in the way that gastric eosinophil count is associated with AP-FGID. The exact cause that can account for this different result is not proven and further succeeding studies are still needed to explain the significance of gastric eosinophilia in pediatric AP-FGID.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Histopathological findings of the present study, confirming that antral eosinophils were significantly activated in children with FD, are consistent with the results of a previous study. 37 The results of this present study is different with that of previous studies except for Friesen et al's study, in the way that gastric eosinophil count is associated with AP-FGID. The exact cause that can account for this different result is not proven and further succeeding studies are still needed to explain the significance of gastric eosinophilia in pediatric AP-FGID.…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, eosinophil densities of children with FD in our study was relatively lower in comparison to those from two previous studies, which report a mean eosinophil density of 7.1 ± 5.5/HPF in the antrum of children with FD, and 10.3 ± 10.1/HPF in the antrum and 21.2 ± 11.5/HPF in duodenal bulb of children with FD. 36,37 In addition, in the present study, we graded the intensity of neutrophil and mononuclear cell infiltration in the stomach using the updated Sydney classification, and compared gastric eosinophil counts with infiltrates of neutrophil and mononuclear cells in order to determine if the degree of eosinophil infiltration correlated with that of other inflammatory cell infiltrations. Accordingly, we were able to verify the association of tissue eosinophil counts with histologic inflammation in the gastric antrum and body, because our study revealed significant correlations between tissue eosinophil counts and histologic inflammation in the gastric antrum and body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few papers show that the gastric and duodenal eosinophil density was increased in children with functional GI disorders. 4,5 This article showed similar results in pediatric patients with functional GI disorders, however, the diagnosis was based on the Rome III criteria, and excluded food allergy, asthma, atropic dermatitis, and rhinitis before the diagnosis. H. pylori infection group showed high eosinophils in the stomach and duodenum, but no statistical significance.…”
mentioning
confidence: 74%
“…For example, EGG abnormalities in children and adolescents with FD are independent of chronic gastritis, but associated with antral mast cell and eosinophil density [121,122] . Likewise, in children with FD, increased antral mast cell density is associated with slower gastric emptying [121] . As alluded to previously, the stress response also has effects on electromechanical function.…”
Section: Mechanisms Of Electromechanical Dysfunctionmentioning
confidence: 99%